Unraveling health challenges in the interior: public perceptions of Health Service Accessibility and its implications - Indriyatmi, RR. Retno (Journal of Public Health Indonesian, 2025)
Access to healthcare services in remote areas remains a significant challenge that impacts community well-being. This study explores community perceptions of healthcare accessibility, identifies the main barriers, and examines their implications. Using a qualitative approach, data were collected through in-depth interviews with community members, local medical personnel, and relevant stakeholders. The findings reveal that the long distances to healthcare facilities, limited transportation, shortage of medical personnel, and lack of medicine and medical equipment are the primary obstacles. Due to these limitations, many residents prefer traditional medicine, which is perceived as more accessible and affordable. Additionally, the community expressed hopes for improvements in healthcare infrastructure, such as the assignment of permanent medical staff, more comprehensive facilities, and better access to medical transportation. This study highlights the need for policy interventions to address these disparities and promote more equitable access to healthcare services. By understanding the lived experiences of people in remote areas, this research contributes to the development of sustainable solutions aimed at improving the quality of healthcare services and overall community well-being.